PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG, DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN TEXTILE DAN GARMENT DI BURSA EFEK INDONESIA PERIODE 2015 – 2018 - Ambarsari, Surya Putri; Wardiningsih, Suprihatmi Sri; Utami, Setyaningsih Sri (Universitas Slamet Riyadi, 2019)
This study aims to determine the effect of cash turnover, accounts receivable turnover, and inventory turnover on profitability (ROA). the type of data used is secondary data taken by the documentation method by accessing the site www.idx.co.id, and the site of each company. Data analysis techniques using the classic assumption test, multiple linear regression, t test, F test, and the coefficient of determination. the results of the research show that cash turnover partially has a significant effect on profitability, whereas accounts receivable turnover and inventory turnover have no significant effect on profitability. Simultaneous cash turnover, accounts receivable turnover, and inventory turnover have no significant effect on profitability.